INVESTIGATING THERMAL VOLTAGE CONVERTERS (TVCS) CORRECTION FACTORS THROUGH ELECTRICAL SIMULATION AND MODELING - Mamdouh, S. Saeed; Mamdouh, Hermach; Ali , Sharaf Elrahman (International Journal of Allied Sciences (IJAS), 2022)
Thermal voltage converters (TVCs) are essential components in various industries, including power generation, aerospace, and automotive applications, due to their ability to measure AC voltage accurately. However, TVCs are inherently susceptible to errors that can arise from factors such as temperature, frequency, and waveform. Consequently, determining correction factors is imperative to improve the accuracy and reliability of TVC measurements. This study aims to investigate the correction factors for TVCs through electrical simulation and modeling. By employing state-of-the-art electrical simulation tools and advanced modeling techniques, a detailed analysis of the factors affecting TVC performance will be conducted. This analysis will enable the identification of the most significant sources of error in TVC measurements and the development of appropriate correction factors to mitigate these errors. The results of this investigation will have a profound impact on the accuracy and reliability of TVC-based measurements in various industries, ultimately leading to improved efficiency and safety in power generation, aerospace, and automotive applications. Furthermore, the insights gained from this study can be applied to other electrical measurement devices, thereby contributing to the advancement of electrical engineering knowledge and practice